2022
DOI: 10.1093/eurjpc/zwac056.275
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and return-to-play in junior competitive athletes: is systematic cardiac screening needed?

Abstract: Funding Acknowledgements Type of funding sources: None. Background SARS-CoV-2 infection might be associated with cardiac complications in low-risk populations, such as in competitive athletes. However, data obtained in adults cannot be directly transferred to preadolescents and adolescents that are less susceptible to adverse clinical outcomes and are often asymptomatic. Purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…They concluded that echocardiography should be reserved for those with cardiopulmonary symptoms or ECG abnormalities. 16 Initial findings at our center suggested no evident signs of myocardial involvement on CMR examination in twelve elite athletes who recovered from COVID-19. 17 By broadening our research to 147 subjects, definite signs of myocarditis were as scarcely prevalent as 1.4% in the whole cohort.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…They concluded that echocardiography should be reserved for those with cardiopulmonary symptoms or ECG abnormalities. 16 Initial findings at our center suggested no evident signs of myocardial involvement on CMR examination in twelve elite athletes who recovered from COVID-19. 17 By broadening our research to 147 subjects, definite signs of myocarditis were as scarcely prevalent as 1.4% in the whole cohort.…”
Section: Discussionmentioning
confidence: 87%
“…Cavigli et al have recently reported their experiences with junior competitive athletes wherein a cohort of 571 subjects found that half of the athletes had had only mild symptoms and pericardial involvement was rare, examined by transthoracic echocardiography. They concluded that echocardiography should be reserved for those with cardiopulmonary symptoms or ECG abnormalities 16 …”
Section: Discussionmentioning
confidence: 99%
“…Among 1597 collegiate athletes in the Big Ten COVID-19 Cardiac Registry, the prevalence of clinical myocarditis with a symptombased screening strategy was 0.3%, whereas the use of MRI increased the prevalence of all (both clinical and subclinical) myocarditis to 2.3% [24]. Other studies have shown similar results, reporting a 0.7-3.3% prevalence of myocarditis or pericarditis following COVID-19 infection, with results varying based on the evaluation strategy [ There are few reports evaluating the prevalence of COVID-19-related cardiac disease in younger patients, though some suggest a similar prevalence to that seen in older patients [26].…”
Section: Return To Athletic Activities Following Severe Acute Respira...mentioning
confidence: 83%
“…Although these numbers are far lower than those initially reported, they suggest a measurable risk of COVID-19-related cardiac disease following apparent recovery from acute COVID-19. There are few reports evaluating the prevalence of COVID-19-related cardiac disease in younger patients, though some suggest a similar prevalence to that seen in older patients [26].…”
Section: Return To Athletic Activities Following Severe Acute Respira...mentioning
confidence: 99%
“…(62,(133)(134)(135)(136)(137)(138) These "expert opinions" were initially based on no data to support the guidelines, but recently some data has become available. (139)(140)(141) The more recent guidelines were only for athletes with SARS-CoV-2 infection and did not focus on all ARinf (irrespective of the pathogen responsible for the ARinf). They have not consistently considered the key concepts and the 3 steps in the RTS decision making process, as discussed above.…”
Section: The Scientific Basis For Rts Decisions After An Arinf In Ath...mentioning
confidence: 99%